Seronegativity to polio viruses among previously immunized adult candidates to solid organ transplantation - Luciana Gomes Pedro Brandão (Brazilian Journal of Infectious Diseases, 2018)
In the current effort to eliminate polio from the world, it is important to recognize and vaccinate susceptible groups, especially immunocompromised patients living in countries where attenuated polio vaccine is still used. In this report, we describe the frequency of protective antibodies in a small sample of adult SOT candidates in whom previous vaccination could be ascertained. Patients included in this report were selected among the participants of an ongoing prospective study carried out at the Reference Center for Special Immunobiologicals of the Evandro Chagas National Institute of Infectious Diseases in Rio de Janeiro, Brazil. Among the first 100 patients enrolled in this study, only seven adult SOT candidates had proven polio vaccination at childhood. Three of these seven patients (43%) had no protective antibody titers to one or more poliovirus subtype before solid organ transplant. Proven childhood vaccination against polio does not reliably provide lifelong protective antibody titers for adult SOT candidates and should not be used as a criterion to analyze the need for vaccination in this population. Keywords: Poliomyelitis, Immunity, Solid organ transplantation